2008
DOI: 10.2136/sssaj2006.0313
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nitrogen Transformations Under Alternative Management Strategies in Appalachian Forests

Abstract: Once subject to frequent fi re and strongly N limited, the forests of the Appalachian Mountain region of eastern North America have experienced almost a century of fi re suppression, and changes in tree species composition, understory density and composition, and accumulations of detritus have paralleled the changes in fi re frequency. In an effort to restore these ecosystems and reduce wildfi re hazard, alternative management strategies (prescribed fi re, mechanical fuel reduction, and a combination of both) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…As expected, fire had significant negative impacts overall on soil respiration and N mineralization. Consistent with the results of the current study, many previous studies also noted that fire decreased soil C and N mineralization (Choromanska and DeLuca, 2001;Coates et al, 2008;Hamman et al, 2008;Antunes et al, 2009). The decrease in soil organic C and the increase in recalcitrant materials likely caused the decrease in C and N mineralization.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, fire had significant negative impacts overall on soil respiration and N mineralization. Consistent with the results of the current study, many previous studies also noted that fire decreased soil C and N mineralization (Choromanska and DeLuca, 2001;Coates et al, 2008;Hamman et al, 2008;Antunes et al, 2009). The decrease in soil organic C and the increase in recalcitrant materials likely caused the decrease in C and N mineralization.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have reported no response or a transient increase in plant available nutrients following prescribed fire in mixed-hardwood forests in Appalachian forests Boerner et al, 2000Boerner et al, , 2004Hubbard et al, 2004;Coates et al, 2008). Others have reported significant increases in available nutrients following burning Boerner and Brinkman, 2005).…”
Section: Soil and Soil Solution Nutrient Responsesmentioning
confidence: 99%
“…They found that the already high rates of N mineralization were increased significantly by whole-tree harvest treatments, and the addition of N, Ca, and Mg fertilization with whole-tree harvesting resulted in the highest rates of nitrification. Coates et al (2008) showed that mechanical thinningfrom-below treatments resulted in increases in extractable total inorganic N, net N mineralization, and nitrification during the first post-treatment year. Elevated leaching of Ca and Mg often occurs with increased nitrification.…”
Section: Maintaining Site Productivitymentioning
confidence: 99%